"Living the brand" som en brandorienteret dialogisk praxis: Om udvikling af medarbejdernes brandorienterede dømmekraft - Dorte Hermansen (Copenhagen Business School (CBS), 2009)
– How can service companies get their employees to `live the brand'? This thesis answers this question through a dialogue between practice and theory. It investigates the potential of philosophical-dialogical methods to transform abstract brand values into action in corporate branding praxis at TDC and explores opportunities to apply the methods in context of service companies in general. It develops an understanding of corporate branding as an organisational and cultural project in which collective dialogue-processes serve as the main sensemaking process.
hdl:10398/7813
Keywords: 650